Engineering a membrane protein chaperone to ameliorate the proteotoxicity of mutant huntingtin. - Oh, J.; Catherine, C.; Kim, E.S.; Min, K.W.; Jeong, H.C.; Kim, H.; Kim, M.; Ahn, S.H.; Lukianenko, N.; Jo, M.G.; Bak, H.S.; Lim, S.; et al. (Nature communications, 2025)
Toxic protein aggregates are associated with various neurodegenerative diseases, including Huntington's disease (HD). Since no current treatment delays the progression of HD, we develop a mechanistic approach to prevent mutant huntingtin (mHttex1) aggregation. Here, we engineer the ATP-independent cytosolic chaperone PEX19, which targets peroxisomal membrane proteins to peroxisomes, to remove mHttex1 aggregates. Using yeast toxicity-based screening with a random mutant library, we identify two yeast PEX19 variants and engineer equivalent mutations into human PEX19 (hsPEX19). These variants effectively delay mHttex1 aggregation in vitro and in cellular HD models. The mutated hydrophobic residue in the ?4 helix of hsPEX19 variants binds to the N17 domain of mHttex1, thereby inhibiting the initial aggregation process. Overexpression of the hsPEX19-FV variant rescues HD-associated phenotypes in primary striatal neurons and in Drosophila. Overall, our data reveal that engineering ATP-independent membrane protein chaperones is a promising therapeutic approach for rational targeting of mHttex1 aggregation in HD.